A RISING THREAT – RISK FACTORS AND OUTCOMES RELATED TO INFECTIONS WITH ACINETOBACTER SPECIES - Khurana, Prerna; Baliga, Shrikala; Shenoy M, Suchitra; Mithra P, Prasanna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Acinetobacter species is an important cause of community as well as nosocomial infections with a high mortality rate. The study was done to analyze the risk factors associated with Acinetobacter infections and their outcomes. Methods: The clinical details of 100 patients having infections with Acinetobacter species over a period of 1-year were analyzed for underlying risk factors and outcomes. The antibiotic sensitivity results were interpreted according to the Clinical Laboratory Standards Institute guidelines. Results: Majority of the infections caused by the Acinetobacter species were lower respiratory tract infections, most common being ventilatorassociated pneumonia. 47% of the isolates were multi drug resistant and 26% were extensively drug resistant. There is a significant chance of drug resistance and a poor outcome with intensive care unit (ICU) stay, prolonged hospital stay of more than 7 days, the presence of 5 or more risk factors. Endotracheal intubation and mechanical ventilation were the risk factors for increased drug resistance in the ICU. Drug resistance was also seen more frequently in patients with chronic obstructive pulmonary disease, chronic kidney disease, and patients on post-operative care. Conclusion: The steady increase in drug resistant Acinetobacter species and limited antibiotics available advocates an uncompromising approach toward infection control and a judicious use of antibiotics especially in the ICU. An understanding about the risk factors helps in the appropriate approach and management of the patient. Keywords: Acinetobacter, Risk factors, Invasive procedures, Nosocomial.